If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7(v+6)=-91
We move all terms to the left:
-7(v+6)-(-91)=0
We add all the numbers together, and all the variables
-7(v+6)+91=0
We multiply parentheses
-7v-42+91=0
We add all the numbers together, and all the variables
-7v+49=0
We move all terms containing v to the left, all other terms to the right
-7v=-49
v=-49/-7
v=+7
| 6(8+n)=-12 | | v/2+5=9 | | 2=m/5+2 | | -24=2(a+1) | | 3xX-41=26 | | -(x-8)=26 | | -5=-(5+r) | | Z=-5+8i | | 3(3x-6)=-63 | | 3(3x-6)=63 | | 6x-52=32x | | 3x-6=-24x+48 | | 3x-6=6(4x+8) | | X×y=101 | | 67–4x+6x=100 | | 3x-6=(4x+8) | | 800=x+2/3x | | 5^(2x^2)*5^-x=125 | | -6x+72=18x | | 5^2x^2*5^-x=125 | | (1+8)*x=360 | | x*(1+8)=360 | | 9+3x+4x=12 | | 360=x*(1+8) | | 360=x(1+8) | | 360=(1+8)*x | | 52–3n=37 | | 3(5x+4)=7(-3x+12) | | x+56*2=5 | | 5(7x+4)=3(5x+6)+42 | | 4x-40=24x | | 5x-6=7(-7x+30) |